Spatial Development and Mobility Frictions in Latin America : Theory-Based Empirical Evidence - Conte, Bruno; Ianchovichina, Elena (World Bank, Washington, DC, 2022)
Using fine-grained spatial data and a dynamic spatial general equilibrium model, this paper assesses the magnitude of mobility frictions in Latin America as well as the effects of their reduction on spatial development in the region. The results suggest that in most Latin American countries, migration frictions calibrated based on spatially differentiated initial utility are on average smaller and less dispersed than those obtained assuming uniform within-country initial utility. A reduction in trade costs due to optimal investments in road infrastructure in most Latin American countries increases the present discounted value of real per capita income on average in the region by 15.1 percent. This effect is larger than the effects obtained with static quantitative trade models because of substantial dynamic gains. By contrast, a reduction in migration entry costs in the most productive and more populous locations in the Latin American countries has a negligible effect on the present discounted value of the region’s real per capita income, reflecting the relatively small dispersion in domestic migration frictions and their relatively low levels in top locations. In both counterfactuals, the welfare increases are significantly larger than the increases in real per capita output because the reductions in mobility frictions allow people to relocate to areas with better amenities and therefore derive higher utility. These results suggest that trade costs, not migration barriers, represent a major constraint to the efficient spatial distribution of economic activity and growth in Latin America.